2007
DOI: 10.1080/13693780701261614
|View full text |Cite
|
Sign up to set email alerts
|

Putative structure and characteristics of a red water-soluble pigment secreted byPenicillium marneffei

Abstract: The dimorphic fungus, Penicillium marneffei, produces and secretes a brick red pigment, during growth at temperatures below 30 degrees C. It generally diffuses into commonly used media like Sabouraud dextrose agar and malt extract agar. The pigment was purified by reverse-phase liquid chromatography and subjected to structural determination by elemental and spectral analysis using atomic absorption (AAS), ultra violet and visible (UV-VIS), fluorescence, infra red (IR), nuclear magnetic resonance (NMR) and tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…This is in line with experiments that showed that amino acids can be conjugated to monascorubrin and rubropunctatin under specific conditions without enzymatic catalysis 20 . The conclusions drawn on the identity of the red pigment in the present study is in contrast to that of a previous article by Bhardwaj et al , which claimed that the red pigment of P. marneffei structually resembled herquinone and appeared as a dimer through disulfide bond 21 . In the present study, such a compound was not observed in wild type P. marneffei and the knockdown mutants.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with experiments that showed that amino acids can be conjugated to monascorubrin and rubropunctatin under specific conditions without enzymatic catalysis 20 . The conclusions drawn on the identity of the red pigment in the present study is in contrast to that of a previous article by Bhardwaj et al , which claimed that the red pigment of P. marneffei structually resembled herquinone and appeared as a dimer through disulfide bond 21 . In the present study, such a compound was not observed in wild type P. marneffei and the knockdown mutants.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies report the production of a herqueinone-like pigment from Talaromyces marneffei (formerly known as Penicillium marneffei), Monascus-like azaphilone pigments (N-glutarylmonascorubramine and N-glutarylrubropunctamine) from Talaromyces purpureogenus (formerly known as Penicillium purpureogenum), industrially important red pigments (mitorubrin, monascorubrin, PP-R, glauconic acid, purpuride, and ZG-1494α) from Talaromyces atroroseus, trihydroxyanthraquinones (emodin, erythroglaucin, and catenarin) from Talaromyces stipitatus, and a xanthone dimer (talaroxanthone) from Talaromyces sp. (Figure 3b) [100,101,103,107,109]. An uncharacterized red pigment was discovered from Talaromyces siamensis under submerged fermentation [71].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%
“…Extracted pigment samples were purified and run in Ultimate TM 3000 HPLC, following the method mentioned in a similar research article (Bhardwaj et al 2007). As Liquid chromatography-mass spectrometry (LC-MS) method is required to have an idea about the chemical structure and MS attachment was not available; the obtained LC curve was compared with some similar coloured natural pigment HPLC analysis.…”
Section: Hplc Analysis Of Extracted Pigmentmentioning
confidence: 99%